IMPLEMENTASI PENDEKATAN AUTHENTIC LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SMK KOTA BANDAR LAMPUNG - Zainal, Vetri Yanti; Rahmawati, Fanni; Rahmawati, Rahmawati (STKIP PGRI Bandar Lampung, 2021)
The learning approach at Vocational High Schools (SMK) in its activities has not used the authentic learning approach but is still only limited to learning with a conventional approach. This study aims to determine the implementation of the Aunthetic learning approach to improve students' critical thinking skills in SMK Kota Bandar Lampung. The type of research to be carried out is quasi-experimental research with pretest-posttest design. The population in this study were students of class X SMK in Bandar Lampung and the sample in this study was the school of SMK 9 class XI BDP, by taking the research sample technique with the simple technique. random sampling was obtained by class XI majoring in online business and marketing at SMK Bandar Lampung. The analysis results obtained for the Post-Test Normality Test Based on the above test results using SPSS 16.0, it is known that the significance level at Shapiro-Wilk at the post test class XI BDP 1 is greater than 0.210> 0.05. Likewise, in class XI BDP 2, it is known that the significance level at Shapiro-Wilk at the post test is greater than (p> 0.05) or 0.410> 0.05. Homogeneity test in the Post-Test, it is known that the level of significance of the posttest is greater than 0.05 (0.426> 0.05). Based on the results of the Hypothesis Test, the results of the research on the t test obtained the t value of 0.217 and the t table with df (n-2) of 0.107. So it can be concluded that the use of the authentic learning approach can improve students' critical thinking skills.